Structural studies, dielectric and electrical properties of (1-x) Pb(Zr0.52Ti0.48)O3– xCoFe2O4 multiferroics materials - Ahabboud, Malika; Gouitaa, Najwa; Ahjyaje, Fatimazahra; Abdi, Farid; Haddad, Mustapha; Lamcharfi, Taj-dine (Arabian journal of chemistry, 2024)
This work aimed to develop a better combination of PbZr0.52Ti0.48O3 (PZT) and CoFe2O4 (CFO) ceramics with enhanced structural, dielectric, and electric properties. For this aim, (1-x)PZT-xCFO nanocomposites at (0.00, 0.10, 0.20, 0.30, 0.40, 0.50, and 1.00) were synthesized using the combination before calcination of sol–gel (for PZT ceramic) and solid-state (for CFO material) methods. The powder X-ray diffraction analysis reveals that the CFO crystallizes in a spinel cubic structure with the Fd3m space group structure, while the PZT compound crystallizes in two tetragonal and rhombohedral structures with P4mm and R3m space groups respectively, which is confirmed by Raman spectra which also demonstrate that CFO content in (1-x)PZT-xCFO composites affects the vibration types. The scanning electron micrographs (SEM) show that the grains are homogeneous and irregular, with several pores on the surface of ceramics. The dielectric properties of the ceramics were investigated as a function of temperature (from 25 to 500 °C) and frequency (from 100 Hz to 2 MHz) using complex impedance spectroscopy. It shows that with the increase of CFO ratio, the dielectric permittivity values increase in the composites until the composition corresponding to x = 0.3 From 485 to 1620 at 5KHz) and then decreases until 65 for x = 1.00. The dielectric constant a function of frequency at different temperatures of (1-x)CFO-xPZT composites indicated that the dielectric constant increases with the increase of CFO content. The impedance spectrum is characterized by simple semicircular arcs and shows a non-Debye relaxation. The electric conductivity reveals that as CFO increases, conductivity remains constant, and the frequency dependence of conductivity shifts away from high frequencies. Also, the value of the exponent n decreases from 1.44 to 0.26 with an increasing CFO concentration. The activation energy is between 0.32 and 0.16 which confirms that electron hopping is responsible for electrical conduction.